2003
DOI: 10.1093/jurban/jtg079
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of STIs/HIV at the Partnership Level: Beyond Individual-Level Analyses

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 44 publications
0
53
1
Order By: Relevance
“…Promoting and encouraging dyadic communication, particularly on HIV-related issues and condom use prior to sexual intercourse, should be considered. Indeed, several studies among both heterosexual and homosexual populations have confirmed that the greater the communication regarding safer sex within sexual dyads, the higher the level of condom use observed (Greene & Faulkner, 2005;Gorbach & Holmes, 2003;Noar et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Promoting and encouraging dyadic communication, particularly on HIV-related issues and condom use prior to sexual intercourse, should be considered. Indeed, several studies among both heterosexual and homosexual populations have confirmed that the greater the communication regarding safer sex within sexual dyads, the higher the level of condom use observed (Greene & Faulkner, 2005;Gorbach & Holmes, 2003;Noar et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…MSM, men who have sex with men; MSM-EP = MSM recruited from entertainment places; MSM-MP = MSM recruited from massage parlors; TG-SP = transgender women who congregated and/or sought sexual partners on streets/parks. Eaton et al, 2009;Gorbach & Holmes, 2003;Mi et al, 2007;Nemoto et al, 2004;Praptoraharjo, 2011). Our study also demonstrates that the use of club drugs with sexual partners is associated with lower likelihood of condom use, another finding consistent with prior studies (Boeri et al, 2004;Buchbinder et al, 2005;Diaz et al, 2005;Lyons et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, given the potential effect of recent exchange of sex for money or drugs, consideration should be given to amending the checklist to include directed questions about sex exchange and other relational contexts. In our sample there were clearly underlying decisions about when and with whom safer sex practice would or would not occur, often within concurrent multiple sexual relationships (see also Gorbach and Holmes 54 ). Contextual factors as well as individual psychological dispositions, motivations, and behaviors need to be considered in order to design effective interventions.…”
Section: -63mentioning
confidence: 99%
“…5 Two sexual behaviors are driving the heterosexual HIV epidemic propagation in the USA: unprotected vaginal or anal sex 6,7 and concurrent partnering. [8][9][10] Several factors have been found to reduce consistent condom use among heterosexual men regardless of race/ethnicity, including reduced sexual pleasure and concerns about sexual performance, [11][12][13] negative outcome expectancies, 14,15 condom use selfefficacy, [16][17][18][19] attitudes towards condoms, 13,17,19 and risk perceptions. [20][21][22] Condom use also varies by partnership type, 23 relationship duration, 24,25 use of other contraceptive methods, 26,27 and sexual communication, [28][29][30][31] as well as drug and alcohol use.…”
Section: Introductionmentioning
confidence: 99%